2023
DOI: 10.3389/fimmu.2023.1142830
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pathology and transcriptome profiling reveal features of immune response of acutely infected and asymptomatic infected of carp edema virus in Koi

Abstract: Koi sleepy disease (KSD) is a high mortality and infection viral disease caused by carp edema virus (CEV), which was a serious threat to aquaculture of common carp and export trade of Koi worldwide. Asymptomatic infection is an important cause of the difficulty in preventing KSD and its worldwide spread, because asymptomatic infection can be activated under appropriate condition. However, the understanding of the molecular correlates of these infections is still unknown. The purpose of this study was to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This contrasts with the finding of the study by Adamek et al . ( 2 ) concerning carp edema virus transmission, in which common carp gill tissue showed higher virus loads than intestine, kidney, skin or spleen tissue; the highest levels of viral nucleic acid were also found in the gills of infected koi in research by Ouyang et al ( 11 ).…”
Section: Discussionmentioning
confidence: 98%
“…This contrasts with the finding of the study by Adamek et al . ( 2 ) concerning carp edema virus transmission, in which common carp gill tissue showed higher virus loads than intestine, kidney, skin or spleen tissue; the highest levels of viral nucleic acid were also found in the gills of infected koi in research by Ouyang et al ( 11 ).…”
Section: Discussionmentioning
confidence: 98%
“…Employing cultivated CEV for in vivo testing could be efficient for studies focused on subclinical infection. In fact, host–pathogen interaction and immune‐derived markers might be used somewhat interchangeably depending upon the severity of CEV infection, which also controls the manifestation of symptoms (Ouyang et al., 2023). Although large doses of cultivated CEV were used (i.e., >10 7 –10 8 ) to experimentally challenge the fish variants, only carp strains from which the primary cultures were derived (R × T) or those ancestrally related to them (AS) showed sporadic positive cases, and then rather at a mid‐stage of infection (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the aforesaid study have found a positive relationship between the increasing size of a virus particle and a larger contact interface with the target cell that could facilitate Employing cultivated CEV for in vivo testing could be efficient for studies focused on subclinical infection. In fact, host-pathogen interaction and immune-derived markers might be used somewhat interchangeably depending upon the severity of CEV infection, which also controls the manifestation of symptoms (Ouyang et al, 2023).…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although different viruses can cause the disease, the clinical signs observed in infected fish are similar in terms of having gill necrosis and deposits of thick mucus under the gill covers being the most prominent (Bergmann et al, 2006;Granzow et al, 2014;Zhu et al, 2019). It is noteworthy that even though these viruses were identified decades ago, they continue to spread worldwide (Bergmann et al, 2020;Ouyang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%